2012
DOI: 10.1016/j.bmcl.2011.12.102
|View full text |Cite
|
Sign up to set email alerts
|

New ionic derivatives of betulinic acid as highly potent anti-cancer agents

Abstract: Betulinic acid is a natural compound with high in vitro cytotoxicity toward many cancer cells. However, the poor water solubility of this compound hampers an effective in vivo cancer study. We prepared new ionic derivatives of betulinic acid with higher water solubilities, without losing the structural integrity and functionality of this compound. As a result, these new ionic derivatives have shown much higher inhibitory effects against different cancer cell lines such as melanoma A375, neuroblastoma SH-SY5Y a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…These compounds maintain the structure of BetA but have better water solubility. BetA and its derivatives inhibit melanoma cells and a variety of other cancer cells .
…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…These compounds maintain the structure of BetA but have better water solubility. BetA and its derivatives inhibit melanoma cells and a variety of other cancer cells .
…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…3E-(2-Chloroacetoxy)-28-hydroxylup-20(29)-ene (9). A solution of vinyl ether 8 (0.78 g, 1.667 mmol) and chloroacetic acid (0.32 g, 3.333 mmol) in anhydrous CH 2 Cl 2 (30 mL) was treated under Ar with DMAP (0.41 g, 3.333 mmol), stirred for 5 min, treated in one portion with DCC (0.69 g, 3.333 mmol), and stirred for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a series of ionic betulinic-acid derivatives such as ammonium and triphenylphosphonium salts were synthesized. They exhibited significantly higher antitumor and antimicrobial activity than the acid itself [6][7][8][9][10][11][12][13]. Sulfobetaine derivatives of betulinic acid and other lupane-type pentacyclic triterpenoids have not been reported despite the frequent use of the biomimetic sulfobetaine group to design biologically active compounds with antibacterial, antiviral, and antiproliferative properties; to increase the solubility of hydrophobic compounds; and also to construct nanocarriers for targeted drug delivery [14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…In 1995, BA was reported as a highly selective growth inhibitor [18] of human melanoma, neuroectodermal and malignant tumor cells and was reported to induce apoptosis in these cells [19]. At the same time, a large number of BA derivatives have been synthesized to improve anti-HIV activity [20,21], to reduce the organ toxic effect of antitumor drugs [22] and to be evaluated as new anticancer agents [23]. Researchers have demonstrated that the presence of a polar substituent at the C-3 position was essential for the pharmacological activities of pentacyclic triterpenes [24].…”
Section: Introductionmentioning
confidence: 99%